Sampling bias in physiotherapy research - J. A. Hendry (AOSIS, 1986)
In this article the difference between random error (due to sampling variability) and systematic error (or bias) is briefly illustrated. Major types of systematic error which occur due to errors in sampling are discussed briefly with reference to the following study designs: the randomized clinical trial, cohort analytical, cross-sectional, case control and before-after studies.